Tinjauan Praktik Green Supply Chain Management (GSCM) - Junita Junita; Asmawati Asmawati; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
An environmentally friendly supply chain or Green Supply Chain Management (GSCM) is an important issue that is popularly discussed today, related to the reality of continuing environmental damage. The aim of this study is to map the GSCM practices that have been reported by experts. An intensive literature review was undertaken to examine research and practice with respect to the adoption of an environmentally friendly supply chain strategy. The results of the study show that there are three important elements in realizing an environmentally friendly supply chain, namely collaboration, innovation and operation. Further research opportunities are related to the theoretical and multifunctional examination of GSCM, measuring the effectiveness of GSCM application, the ability of small and medium scale industries to apply GSCM.